Perubahan Sitokin Pro-inflamasi setelah Pemberian Jahe Merah pada Mencit dengan Paparan Asap Rokok: Studi In Vivo - Putra, Aditya; Pratama, Farhan (Lembaga Publikasi Ilmiah Nusantara, 2025)
Exposure to cigarette smoke is known to trigger oxidative stress and inflammatory responses, characterized by increased levels of pro-inflammatory cytokines such as Tumor Necrosis Factor-alpha (TNF-α) and Interleukin-6 (IL-6). Excessive inflammatory responses can disrupt cellular homeostasis and contribute to tissue damage. Red ginger contains bioactive compounds, including gingerols and shogaols, which exhibit strong antioxidant and anti-inflammatory activities. This study aims to analyze changes in TNF-α and IL-6 levels in mice following the administration of red ginger extract under cigarette smoke exposure. An in vivo design was used by dividing mice into several groups: a control group, a group exposed to cigarette smoke, and a group exposed to cigarette smoke with red ginger extract treatment. After the treatment period, TNF-α and IL-6 levels were measured through serum analysis using immunological methods. The results showed that mice receiving red ginger extract experienced a significant reduction in TNF-α and IL-6 levels compared to the smoke-exposed group without treatment. These findings indicate that red ginger has potential protective effects by modulating inflammatory responses induced by cigarette smoke exposure. Therefore, red ginger can be considered a natural anti-inflammatory agent for reducing the negative impact of oxidative stress from cigarette smoke.